2022
DOI: 10.1038/s41598-022-26037-w
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial virulence factor interacts with the splicing factor RBM5 and stimulates formation of nuclear RBM5 granules

Abstract: L. monocytogenes causes listeriosis, a foodborne disease that is particularly dangerous for immunocompromised individuals and fetuses. Several virulence factors of this bacterial pathogen belong to a family of leucine-rich repeat (LRR)-containing proteins called internalins. Among these, InlP is known for its role in placental infection. We report here a function of InlP in mammalian cell nucleus organization. We demonstrate that bacteria do not produce InlP under in vitro culture conditions. When ectopically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…While NLSs are expected in eukaryotic organisms, their presence in bacteria is more surprising. Studies have revealed that bacterial proteins with NLSs can play a role in host–microbe interactions and promote bacterial survival (Ma et al, 2020 ; Pourpre et al, 2022 ). Despite this, more research is needed into the origin and function of bacterial NLSs.…”
Section: Bioactivities Of Interestmentioning
confidence: 99%
“…While NLSs are expected in eukaryotic organisms, their presence in bacteria is more surprising. Studies have revealed that bacterial proteins with NLSs can play a role in host–microbe interactions and promote bacterial survival (Ma et al, 2020 ; Pourpre et al, 2022 ). Despite this, more research is needed into the origin and function of bacterial NLSs.…”
Section: Bioactivities Of Interestmentioning
confidence: 99%